Development of the Silicon Drift Detector for Electron Microscopy Applications. (September 2020) - Strüder, Lothar; Niculae, Adrian; Holl, Peter; Soltau, Heike
Abstract: Abstract : In the 50 years since the first mating of semiconductor-based energy-dispersive X-ray spectrometry (EDS) with the scanning electron microscope (SEM), this hybrid instrument has become an indispensable microanalytical tool. In the last two decades a new detector, the silicon drift detector (SDD), has overtaken earlier Si(Li) technology and has made EDS in the SEM and TEM faster and better. This article tells the story of the SDD development and describes improvements in count rate capability, energy resolution, and detector geometry that bring to SEM microanalysis exceptional precision and stability. Quality maps of element distributions can now be obtained in minutes instead of hours.